2018
DOI: 10.3390/ijms19103208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulatory Mechanism of Exocytosis in the Salivary Glands

Abstract: Every day, salivary glands produce about 0.5 to 1.5 L of saliva, which contains salivary proteins that are essential for oral health. The contents of saliva, 0.3% proteins (1.5 to 4.5 g) in fluid, help prevent oral infections, provide lubrication, aid digestion, and maintain oral health. Acinar cells in the lobular salivary glands secrete prepackaged secretory granules that contain salivary components such as amylase, mucins, and immunoglobulins. Despite the important physiological functions of salivary protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 150 publications
(187 reference statements)
0
7
0
3
Order By: Relevance
“…Interestingly, we observed downregulation of a number of genes belonging to the Ras superfamily of GTPases (RAB GTPases). RAB GTPases play critical roles in exocytosis and membrane trafficking including vesicle formation, docking and membrane fusion, all vital functions necessary for proper saliva secretion ( 55 ). More specifically, we observed reduced gene expression levels of Rabac1 and Rab6b in the salivary glands of SS mice compared to control animals ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we observed downregulation of a number of genes belonging to the Ras superfamily of GTPases (RAB GTPases). RAB GTPases play critical roles in exocytosis and membrane trafficking including vesicle formation, docking and membrane fusion, all vital functions necessary for proper saliva secretion ( 55 ). More specifically, we observed reduced gene expression levels of Rabac1 and Rab6b in the salivary glands of SS mice compared to control animals ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ultrastructurally, large secretory granules were accumulated in the acini of diabetes SMGs, and more were scattered in the acini of diabetes PGs. Proteins are the main component of secretory granules and their secretion is a dynamic process comprising synthesis, transport, and secretion (Suzuki and Iwata, 2018). Here, the docked secretory granules in diabetes SMG and PG suggested that the process of secretion is somehow impaired in diabetic condition.…”
Section: Discussionmentioning
confidence: 99%
“…The three pairs of major (submandibular, parotid and sublingual) and minor salivary glands secrete saliva in the mouth. Saliva presents diverse functions, including lubrication, initiation of digestion, and immunity [18]. It is a biofluid rich in water, ions, and several protein groups, including mucins, which are proteins glycosylated, and most have high sialic acid content [19].…”
Section: Salivary Glands and Salivamentioning
confidence: 99%